Ultrasound guided steroid injection of subacromial bursa: morphologic and clinical effects on patients with supraspinatus tendon calcifications - ŞANAL TOPRAK, CANAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Subacromial injection (SAI), due to its ease of application and increased patient tolerability, is one of the preferred invasive therapies. In this study, we aimed to evaluate effectiveness of ultrasound-guided SA I in patients with supraspinatus calcific tendinitis by assessment of roentgenograms and clinical appraisal. Patients and Methods: Thirty-five patients with supraspinatus tendon calcifications as revealed by the roentgenography underwent ultrasound-guided SAL Pre-treatment the Disabilities of the Arm, Shoulder and Hand questionnaire (QuickDASH) scores and Gartner's aassification of calcific tendinitis were obtained. Clinical follow-up was scheduled at 1st, 3rd and 6th months post-treatment along with a single roentgenogram planned at 6th month. Results: A total of 53 SAIs were performed on 36 shoulders, 21 female and 14 male patients. Mean size of calcifications were 12.3 and 7.1 mm, pre-treatment and at 6th month, respectively. Pre and post-injection calcification mean sizes in the group with clinical improvement were 13.6 and 5.7 mm; whereas, in group without diminished symptoms, they were 11.8 and 9.4 mm demonstrating a statistically significant intergroup difference (p<0.05). Pre-injection QuickDASH mean score was 52.2; this showed improvement at 1st, 3rd and 6th months post-treatment; 20.7, 22.2 and 193, respectively. Conclusion: Subacromial injection is a well-tolerated, easily applicable, safe and effective treatment for pain alleviation in supraspinatus calcific tendinitis.
Keywords: Calcific tendinitis; Shoulder joint; Subacromial bursa; Sonography guided injection; Steroid injection; SHOCK-WAVE THERAPY; ROTATOR CUFF; TENDINITIS; SHOULDER; OUTCOMES; LAVAGE